2018
DOI: 10.1002/da.22774
|View full text |Cite
|
Sign up to set email alerts
|

Finding factors that predict treatment-resistant depression: Results of a cohort study

Abstract: BackgroundTreatment for depressive disorders often requires subsequent interventions. Patients who do not respond to antidepressants have treatment‐resistant depression (TRD). Predicting who will develop TRD may help healthcare providers make more effective treatment decisions. We sought to identify factors that predict TRD in a real‐world setting using claims databases.MethodsA retrospective cohort study was conducted in a US claims database of adult subjects with newly diagnosed and treated depression with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 36 publications
8
39
0
Order By: Relevance
“…In addition, our results revealed that anxiety is the strongest predictor of TRD with a high PAF. It is well-known that anxiety and depression/TRD often coexist [ 22 , 23 , 25 ], and that anxiety disorders have been identified as a risk factor of poor treatment response [ 43 ]. A previous study also found that anxiety disorders, particularly panic disorder, are associated with TRD [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results revealed that anxiety is the strongest predictor of TRD with a high PAF. It is well-known that anxiety and depression/TRD often coexist [ 22 , 23 , 25 ], and that anxiety disorders have been identified as a risk factor of poor treatment response [ 43 ]. A previous study also found that anxiety disorders, particularly panic disorder, are associated with TRD [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical comorbidities, including diabetes [ 15 , 16 ], heart diseases [ 17 ], functional gastrointestinal disorders (FGIDs) [ 18 ], thyroid disease [ 19 ], systemic lupus erythematosus (SLE) [ 20 ], and rheumatoid arthritis [ 21 ], have been implicated in the development and prognosis of common mental disorders, especially mood disorders. In addition, a group of anxiety disorders (including panic disorder, generalized anxiety disorder, social anxiety disorder, and obsessive-compulsive disorder), attention deficit hyperactivity disorder (ADHD), substance use disorders (SUDs), and personality disorders were found to be more prevalent in patients with MDD [ 22 25 ], or predictive of worse outcomes or slower remission [ 24 ]. This emergent evidence has indicated that both physical and psychiatric comorbidities might prolong the course of depression and worsen clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our results revealed that anxiety is the strongest predictor of TRD with a high PAF. It is well-known that anxiety and depression/TRD often coexist [22,23,25], and that anxiety disorders have been identi ed as a risk factor of poor treatment response [43]. A previous study also found that anxiety disorders, particularly panic disorder, are associated with TRD [44].…”
Section: Discussionmentioning
confidence: 99%
“…Physical comorbidities, including diabetes [15,16], heart diseases [17], functional gastrointestinal disorders (FGIDs) [18], thyroid disease [19], systemic lupus erythematosus (SLE) [20], and rheumatoid arthritis [21], have been implicated in the development and prognosis of common mental disorders, especially mood disorders. In addition, a group of anxiety disorders (including panic disorder, generalized anxiety disorder, social anxiety disorder, and obsessivecompulsive disorder), attention de cit hyperactivity disorder (ADHD), substance use disorders (SUDs), and personality disorders were found to be more prevalent in patients with MDD [22][23][24][25], or predictive of worse outcomes or slower remission [24]. This emergent evidence has indicated that both physical and psychiatric comorbidities might prolong the course of depression and worsen clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Women with psychosis, bipolar disorder, or dementia before the index date (i.e., the date of the first depression diagnosis during pregnancy or 6 months after a delivery) were excluded to ensure that any antipsychotic received was for the treatment of depression and not for the treatment of psychosis. Women with bipolar disorder were excluded because when TRD is studied and defined this type of depression is often excluded [19, 20].…”
Section: Methodsmentioning
confidence: 99%